Large-bore Vascular Closure: New Devices and Techniques - Maarten P van Wiechen; Jurgen M Ligthart; Nicolas M Van Mieghem (Interventional Cardiology: Reviews, Research, Resources)
Endovascular aneurysm repair, transcatheter aortic valve implantation and percutaneous mechanical circulatory support systems have become valuable alternatives to conventional surgery and even preferred strategies for a wide array of clinical entities. Their adoption in everyday practice is growing. These procedures require large-bore access into the femoral artery. Their use is thus associated with clinically significant vascular bleeding complications. Meticulous access site management is crucial for safe implementation of large-bore technologies and includes accurate puncture technique and reliable percutaneous closure devices. This article reviews different strategies for obtaining femoral access and contemporary percutaneous closure technologies.